Activation of Melanocortin Receptors MC1 and MC5 Attenuates Retinal Damage in Experimental Diabetic Retinopathy. (12th January 2016) - Rossi, S.; Maisto, R.; Gesualdo, C.; Trotta, M. C.; Ferraraccio, F.; Kaneva, M. K.; Getting, S. J.; Surace, E.; Testa, F.; Simonelli, F.; Grieco, P.; Merlino, F.; et al.
Abstract : We hypothesize that melanocortin receptors (MC) could activate tissue protective circuit in a model of streptozotocin- (STZ-) induced diabetic retinopathy (DR) in mice. At 12–16 weeks after diabetes induction, fluorescein angiography (FAG) revealed an approximate incidence of 80% microvascular changes, typical of DR, in the animals, without signs of vascular leakage. Occludin progressively decreased in the retina of mice developing retinopathy. qPCR of murine retina revealed expression of two MC receptors, Mc1r and Mc5r . The intravitreal injection (5 μ L) of the selective MC1 small molecule agonist BMS-470539 (33 μ mol) and the MC5 peptidomimetic agonist PG-901 (7.32 nM) elicited significant protection with regular course and caliber of retinal vessels, as quantified at weeks 12 and 16 after diabetes induction. Mouse retina homogenate settings indicated an augmented release of IL-1 α, IL-1 β, IL-6, MIP-1 α, MIP-2 α, MIP-3 α, and VEGF from diabetic compared to nondiabetic mice. Application of PG20N or AGRP and MC5 and MC1 antagonist, respectively, augmented the release of cytokines, while the agonists BMS-470539 and PG-901 almost restored normal pattern of these mediators back to nondiabetic values. Similar changes were quantified with respect to Ki-67 staining. Finally, application of MC3 -MC4 agonist/antagonists resulted to be inactive with respect to all parameters under assessment.